Cross-culture learning via massive open online courses for higher education - Norazah Mohd Nordin,; Helmi Norman, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Cross-cultural learning in higher education involves providing an equitable interaction of diverse cultures and moving towards generation of shared cultural expression through dialogue and mutual respect at local, national, regional, and international levels. This can be achieved via the use of massive open online courses (MOOCs), which has received much interest over recent years. Yet, in designing successful cross-cultural learning via MOOCs, there are three important aspects that are worth to be considered. They are instructional design, learning content and tasks design as well as technological acceptance of MOOCs. This paper focuses its’ discussion on these three aspects via a study conductedby online surveys conducted with 135 undergraduates at a local university. Findings indicated that with regards to learning content design, types of video lectures that can enhance MOOC learning are animations and live action videos that are integrated with casual style of communication and humor aspects. Findings also revealed that in terms of learning task design, fully and loose structured learning tasks are both of equal importance and both high and low autonomy are important. The paper concludes with issues and challenges in MOOC development and implementation.